Genetic Identification and Phylogenetic Relationship of Fish Species at Panjnad, Abbasia, and Abu Dahbi Canals (Punjab, Pakistan) Based on Mitochondrial COI Sequences - Naz, Saima; Ahmad Manan Mustafa Chatha; Danabas, Durali; Kousar, Naila; Ashraf, Naeem Mehmood (Current Trends in OMICS, 2022)
Fish is an extremely nutritious food abundant in important minerals, vitamin D, proteins, and omega-3 fatty acids. Mislabeling of fish products is a major problem in the fish industry. It affects market prices and causes price fluctuations. Phylogenetic analysis of nucleotide sequences could be used to verify the identity of misidentified fish species. In this study, five species (Cirrhinus mrigala, Hypophthalmichthys molitrix, Actinopterygii sp. [OC218 and OC21] and Mastacembelus armatus) were identified based on their phylogenetic analysis using the Cytochrome C Oxidase 1 (COI) gene amplified through PCR. The average product size was 658 base pairs. The comparison of obtained sequences was implemented through the National Center for Biotechnology Information (NCBI) database and Basic Local Alignment Search Tool (BLAST). The most similar sequences were downloaded for comparison with the obtained sequencing results. By using Molecular Evolutionary Genetics Analysis (MEGA X) the rate of different transitional substitutions was determined to be 11.33, while the rate of transversional substitutions was determined as 6.83. Transition/Transversion bias was 0.83. Kimura 2-parameter (K2p) model was used for the estimation of this substitution pattern. Since most freshwater fish species belonged to the same order or family, phylogenetic tree analysis indicated that they should be grouped together. By using the InterPro data that provides functional analysis of protein sequences by categorizing them into families, the activity and regulatory pathways of COI gene were identified to show its activity on protein level, especially for performing some important physiological functions. Each species of fish can be identified based on their speciation, nodes position, and distance from their parent nodes. Based on the closest phylogenetic relations, a DNA sequence-based study was developed for the accurate identification of fish species.